2020
DOI: 10.1101/2020.05.12.091298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of neutralizing antibodies from a SARS-CoV-2 infected individual

Abstract: 22B cells specific for the SARS-CoV-2 S envelope glycoprotein spike were isolated from a 23 COVID-19-infected subject using a stabilized spike-derived ectodomain (S2P) twenty-one 24 days post-infection. Forty-four S2P-specific monoclonal antibodies were generated, three 25 of which bound to the receptor binding domain (RBD). The antibodies were minimally 26 mutated from germline and were derived from different B cell lineages. Only two 27 antibodies displayed neutralizing activity against SARS-CoV-2 pseudo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 43 publications
8
75
0
Order By: Relevance
“…were over-represented . Other studies have also reported anti-SARS-CoV-2 mAbs derived from these genes (Brouwer et al, 2020;Cao et al, 2020;Chi et al, 2020;Ju et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Wu et al, 2020c;Zost et al, 2020).…”
Section: A Cryo-em Structure Of a Monoclonal Fab-s Protein Complex Rementioning
confidence: 96%
“…were over-represented . Other studies have also reported anti-SARS-CoV-2 mAbs derived from these genes (Brouwer et al, 2020;Cao et al, 2020;Chi et al, 2020;Ju et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Wu et al, 2020c;Zost et al, 2020).…”
Section: A Cryo-em Structure Of a Monoclonal Fab-s Protein Complex Rementioning
confidence: 96%
“…Recent studies have shown that related, potently neutralizing monoclonal antibodies that recognize the SARS-CoV-2 receptor binding domain (RBD) are often elicited in SARS-CoV-2 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These antibodies have great potential to be clinically impactful in the treatment and prevention of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have begun to unravel the antibody response to SARS-CoV-2 beyond a simple "yes or no" answer [9][10][11][12][13][14][15][16][17][18] . Here, we hypothesized that by examining the antibody profile in patient's serum in terms of antigens, antibody isotypes (IgG, IgM, and IgA), and neutralization, we would be able to identify specific signatures associated to effective SARS-CoV-2 neutralization.…”
Section: Introductionmentioning
confidence: 99%